The main directions of prevention of deviant behavior in the era of globalization (Journal of actual problems of jurisprudence, 2018)
The purpose of this article is to determine the benefits and harms of the Internet on the socialization of adolescents and young adults. Defines the role of the Internet in the development and education of adolescents and young adults. In the process of globalization are considered negative aspects of the new media environment. The focus is on information security for children. Provided recommendations to prevent the negative impact of the Internet on minors.Key words: globalization, minors, delinquency prevention, Internet addiction, suicide.